Combining ability of maize lines with different capacity tolerance to the maize bushy stunt. - Castañón, Guillermo; Jeffers, Dan; Hidalgo, Héctor (Agronomía Mesoamericana, 2006)
This research was carried out to evaluated seven parents and theirs F1’s progenies. The objective was to study the response of the hybrids and parents to infection with the bushy stunt, trasmited for Dalbulus maydis. The results showed that additive effects (GCA) were more important that no-additives effects (SCA). It was found that to grain yield (GY) the best cros ses, were between one resistant ( R) line x susceptible (S) line. The lowest yield grain crosses were observed between R X R or S x S parents or lines. The lines three and five, were the material values of GCA to yield grain. The estimated values for SCA had important role in the hybrid genetic structure. The line two, was the parental that in hybrid combination presented highest SCA values. Lines one and seven, were the lowest materials to GCA.